Effective and safe provocation test for wheat-dependent exercise-induced anaphylaxis (WDEIA) in adults results of testing on 33 cases - Akiko Sugiyama; Takehito Fukushima; Koki Okabe; Kiyotaka Shimada; Kaoru Kojima; Yuko Shigeoka; Satoshi Honjo; Reiko Kishikawa (Frontiers Media S.A., 2024)
Background: Wheat-dependent exercise-induced anaphylaxis (WDEIA) is induced not by the intake of wheat-based food alone, but by the combination of exercise stress and such intake. Provocation tests have been reported to be useful for the diagnosis of this condition, but they are not always accurate. Furthermore, provocation tests are associated with the risk of anaphylactic shock, so safer testing is required.Subjects and methods: Thirty-three patients (mean age 35.5 ± 16.0 years) who underwent provocation tests from April 2019 to July 2023 were included in this study. We investigated associations of their provocation test results with their medical history, blood test results before the provocation tests, exercise load at the time of the test, and severity of the induced symptoms.Results: Symptoms were induced and the diagnosis of WDEIA was made in 28 cases, while 2 cases were confirmed not to have WDEIA. Overall, 25 of the 28 positive cases had symptoms induced by an exercise load greater than 70% of the heart rate calculated by the Karvonen formula, 7 of which required Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) loading to induce symptoms. None of the patients with negative wheat-specific IgE titers and positive gluten and/or ω-5 gliadin ones required NSAIDs loading. No patients required the administration of adrenaline.Conclusion: Wheat-specific IgE as well as gluten and ω-5 gliadin antibody titers are associated with WDEIA symptom severity. Exercise loading with a target heart rate of 70%-90% of that calculated by the Karvonen formula is safe and useful for diagnosis this condition.